Growth and productivity of coppice stands of the European aspen (Populus tremula L.) in fresh and moist fertile forest site types in plain part of Ukraine - Tkach, V. P.; Vysotska, N. Yu.; Kobets, O. V. (Forestry and Forest Melioration, 2019)
Introduction Yield tables serve as a basis for regulatory materials and are used to carry out forest inventory, to develop and plan forestry works, and implement measures aimed at increasing forest productivity. Most yield tables are designed primarily for complete (normal) stands. However, these tables do not take into account regional features of the forest stands growth. Therefore, it is necessary to study features of the growth and development of modal aspen stands in specific forest conditions. The aim of the study was to simulate the course of growth of aspen stands in fresh and moist fertile sites and to compare the productivity of these stands in different climatic zones. Materials and Methods Growth modelling and construction of yield tables were performed according to generally accepted methods by analyzing the subcompartment database of ‘Ukrderzhlisproekt’ Production Association. A total of 2,000 subcompartments of European aspen stands were analyzed. Data processing was carried out in accordance with generally accepted in forestry and forest mensuration methods and methods of mathematical statistics. Results The total area of European aspen stands in the plain forests subordinated to the State Forest Agency is 34,300 hectares. The area of aspen stands in fresh and moist fertile forest site types increases from north to south and makes 11% in Polissia, 57 % in Forest-Steppe, 67 % in Steppe and 36 % totally in the plain part of Ukraine. The European aspen stands of natural coppice origin prevail in fresh and moist fertile forest sites. Mathematical correlations that characterize the growth of European aspen stands of natural coppice origin in fresh and moist fertile forest site types were established and yield tables drafts were developed. The relative indices showed that the aspen stands in Polissia exceed those in the Left-Bank and Right-Bank Forest-Steppes in their stock by 7–10% and 10–29% respectively. At that, this difference gradually decreases with age. Aspen stands in the Left-Bank Forest-Steppe are 3–21% more productive compared to those in the Right-Bank Forest-Steppe. The difference gradually decreases with age as well. The stock of the modal aspen stands in Steppe is 20–29% lower compared to that in Polissia and 6–21% less than that in Forest-Steppe. The age of quantitative maturity of modal European aspen stands of coppice origin was determined by stock change. This indicator is 27 years in Polissia and Forest-Steppe, and 30 years in Steppe. Conclusions The developed yield tables objectively characterize the features of growth and productivity of the European aspen stands of coppice origin in fresh and moist fertile forest site types. It is helpful to use these tables when planning intermediate felling. Aspen stands are the most productive in Eastern Polissia and Left-Bank Forest-Steppe. The comparative analysis of aspen stands stocks in terms of natural zones showed that stands in fresh and moist fertile forest sites have a higher productivity compared to those in fairly fertile forest sites. The quantitative maturity age of aspen stands of coppice origin belongs to the III age class and makes 27 years in Forest-Steppe and Polissia, and 30 years in Steppe. 3 Figs., 4 Tables, 14 Refs.